Spontaneous Reattachment of a Posteriorly Dislocated Endothelial Graft: A Case Report. (3rd March 2013) - Kam, Ka Wai; Young, Alvin L.
Abstract : A thirty-year-old Chinese man with a history of severe trauma to his right eye, with secondary sectoral aniridia and multiple operations including intraocular lens insertion more than fifteen years ago, underwent an uneventful Descemet's Stripping Automated Endothelial Keratoplasty (DSAEK) for his pseudophakic bullous keratopathy in a tertiary hospital in Hong Kong. The nature of his previous operations was unknown to the surgeon at the time of transplant. On postoperative day one, the graft was not present in the anterior chamber. Fundal view was limited because of corneal oedema. B-scan ultrasonography could not detect any definite presence of a donor button in the posterior segment as gas was present in the vitreous cavity. The patient was instructed to lie prone full time, and on postoperative day three, the graft was found to be reattached to the stroma with spontaneous resolution of corneal oedema, indicating restoration of pump function of endothelium graft. This is the first case of spontaneous reattachment of a posteriorly dislocated endothelial graft without surgical intervention or abandonment of the grafted endothelial button.